Strategia kreowania wartości na podstawie określeń kolorystycznych w języku polskim i rosyjskim - Narloch, Andrzej (Przegląd Rusycystyczny, 2018)
СТРАТЕГИЯ ФОРМИРОВАНИЯ ЦЕННОСТЕЙ НА ОСНОВАНИИ ЦВЕТОВЫХ ВЫРАЖЕНИЙ В ПОЛЬСКОМ И РУССКОМ ЯЗЫКАХ Р е з ю м е Настоящая статья посвящена изучению стратегии формирования ценностей в польских и русских цветонаименованиях из сферы маркетинга и торговли. На широком культурном фоне с учетом современных культурных перемен в статье анализируются разные способы языкового выражения названий цветов с помощью нестандартных терминов. Анализ этих выражений дает возможность взглянуть в суть процессов номинации, в которых создатели формируют своеобразную цветовую картину с собственной системой ценностей. THE STRATEGY OF CREATING VALUES ON THE BASIS OF COLOUR DESCRIPTIVE PHRASES IN POLISH AND RUSSIAN S u m m a r y The purpose of this paper is to discuss the strategy of creation of values in Polish and Russian names of colours used in marketing and trade. Different methods of linguistic expression of colours with the use of non-standard phrases is presented in the paper on the background of contemporary cultural and social transformations. The analysis of those phrases allows a thorough study of the nature of nomination process where the author creates a specific picture of colour system referring to the values desired in the contemporary world.